Comparison of Manual and Digital Management Information Systems in the Strategic Planning Process - Andi Indriani Ibrahim; Dhea Daleta; Novryanti Buabangga; Norissa Lawa; Nini Andriani; Ayu Putri Utami; Anita (Universitas Muhammadiyah Palu, 2026)
This study aims to obtain a more comprehensive picture of the differences in the effectiveness of management information systems in supporting the strategic planning process, as well as to evaluate the advantages and limitations of each system in the strategic planning process in two coffee shops. This study uses a qualitative research method with a descriptive approach. The results of the study indicate that digital MIS consistently outperforms manual MIS in every strategic aspect of the business. This difference positions digital MIS as a crucial tool in facing the dynamics of modern business.